GELIAT MEDIA SOSIAL DAN PENGARUHNYA TERHADAP MINAT BERKUNJUNG WISATAWAN - Titi Setiyarti; Grace Felas Silitonga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The influence of social media on tourism has risen, since through it tourists can get information to help them in their travel planning process. This article will focus on looking at the influence of social media on the visiting interest of domestic tourists using indicators proposed by Taprial dan Kanwar (2012), with Nusa Penida as a case study. The research that forms the basis for writing this article was carried out in the fourth quarter of 2020 when the Covid-19 pandemic occurred, hence all the questionnaires were distributed online through Google Forms. The study found that while the variables of ‘accessibility’, ‘speed’, ‘interactivity’, ‘volatility’, and ‘range’ simultaneously have a significant effect, only ‘interactivity’ and ‘range’ have a partially significant positive effect on visiting interest of domestic tourists. Furthermore, although the regression model can statistically be used to determine the interest in visiting domestic tourists, the effect is not large, only 49%, while the remaining 51% is influenced by other factors. This indicates that a deeper research is needed on social media indicators that, directly or indirectly, affect the interest of domestic tourists to visit a particular tourist site such as Nusa Penida.